Metabolic influences on RNA biology and translation. (4th March 2017) - Lee, Chien-Der; Tu, Benjamin P.
Abstract: Protein translation is one of the most energetically demanding processes for a cell to undertake. Changes in the nutrient environment may result in conditions that cannot support the rates of translation required for cell proliferation. As such, a cell must monitor its metabolic state to determine which mRNAs to translate into protein. How the various RNA species that participate in translation might relay information about metabolic state to regulate this process is not well understood. In this review, we discuss emerging examples of the influence of metabolism on aspects of RNA biology. We discuss how metabolic state impacts the localization and fate of different RNA species, as well as how nutrient cues can impact post-transcriptional modifications of RNA to regulate their functions in the control of translation.